2020
DOI: 10.32600/huefd.621553
|View full text |Cite
|
Sign up to set email alerts
|

Konferans Salonunda Dağıtık Biliş: Andaş Çeviri Sürecine Yeni Bir Bakış

Abstract: Dağıtık biliş, bilişsel görevlerin tek bir biyolojik organizmanın kafatası ile sınırlı zihninde gerçekleştirilmesi yerine, bilişin bireysel ve izole zihinden taşarak çevredeki biyolojik/biyolojik olmayan yapılara dağılması/yayılması şeklinde özetlenebilecek bir zihin yaklaşımıdır. Dağıtık biliş, bilgi-işlemsel zihin kuramına tepki olarak ortaya çıkmış; bellek ve dil gibi temel bilişsel yetileri yeniden değerlendirmek için kullanılmış; bilişsel yük boşaltma, geçişken bellek ve tekno-sosyal sistem gibi çeşitli k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Moreover, it is fair to argue that SI is an emotionally taxing activity even without emotional language. Previous studies have identified several external stressors in SI, ranging from speaking rate (Korpal, 2016) to prolonged turns (Klonowicz, 1990;Moser-Mercer et al, 1998), from textual complexity to lexical search under time pressure (Gumul, 2021), from challenging techno-social work environments (Korpal, 2021;Kumcu, 2020;Kurz, 2002) to booth discomfort (Mackintosh, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is fair to argue that SI is an emotionally taxing activity even without emotional language. Previous studies have identified several external stressors in SI, ranging from speaking rate (Korpal, 2016) to prolonged turns (Klonowicz, 1990;Moser-Mercer et al, 1998), from textual complexity to lexical search under time pressure (Gumul, 2021), from challenging techno-social work environments (Korpal, 2021;Kumcu, 2020;Kurz, 2002) to booth discomfort (Mackintosh, 2003).…”
Section: Introductionmentioning
confidence: 99%